Prediction of Across Wind Response of Tall Buildings: An Overview - Kiriparan, B.; Jayasinghe, J.A.S.C.; Dissanayake, U.I. (My University, 2019)
Wind induced lateral loading is one of the vital factors governing the design of tall buildings. Along wind, across wind and torsional responses are three important considerations in wind design of tall buildings. A well-established gust factor approach is adopted in most of the wind design codes to predict the dynamic response of tall buildings in the along wind direction. Along wind predictions using this approach is found to be with reasonable accuracy when the wind flow is not signif icantly affected by neighbouring buildings. However, the applicability of most of the wind design codes are restricted to regular shaped structures with limitation on height or natural frequency. Dynamic motion of tall and slender structures perpendicular to the direction of the wind is known as across wind excitation. This phenomenon can be resulted from three mechanisms and their higher time derivatives such as vortex shedding, incident turbulence mechanism and higher derivatives of cross wind displacement (i.e., galloping, flutter and lock-in). Due to the complex nature of the wind, characteristics of vortices and its interaction with the structure, significant limitations are found among the provisions set out in different international stan dards for the prediction of across wind responses. Though most of the existing codes are capable of predicting the along wind loading to reasonable accuracy, only a few international standards provide provisions for across wind effects. Unlike the along wind responses significant discrepancies are found among the across wind responses estimated by different standards. This paper presents an overview of capabilities and limitations of design provisions available in seven international codes/standards such as BS 6399-2:1997, BS EN 1991-1-4:2005, AS/NZS1170.2:2011, AIJ: 2004, CNS: 2012, ASCE 7-10 and NBCC: 2005 for the prediction of across wind responses. Comparisons of predicted across wind induced response for different building config urations (range of plan aspect ratio form 1–2, height aspect ratio from 4 to 8 and height from 120 to 240 m) are used to explain the influence of methods adopted in each of those wind codes.
Keywords: Tall buildings; Across wind responses; Vortex shedding; Wind design codes